STRATEGI EDUKASI DAN PEMBERDAYAAN DALAM PENCEGAHAN HIV/AIDS PADA REMAJA DAN PEREMPUAN - Dita Nurlatifah; Lilis Lismayanti (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Adolescents are a population group with a high level of vulnerability to HIV/AIDS, influenced by limited knowledge, a tendency to engage in risky behavior, and barriers to accessing accurate information. Therefore, an educational approach is seen as a crucial strategy in prevention efforts. This study aims to improve the effectiveness of health education about HIV/AIDS in improving adolescent knowledge and attitudes through a literature review of public pre,The study results showed that all studies reported a significant increase in adolescents’ knowledge levels after educational interventions, with several studies reporting an increase in knowledge scores ranging from 2–4.5 points and an increase in the proportion of those in the good knowledge category from 39.9% to 60.2%. Educational interventions were also shown to have a positive impact on developing attitudes that are more supportive of preventive behaviors and increasing adolescents’ motivation to avoid the risk of transmission. The intervention’s effectiveness was most prominently seen in community-based programs that combined lecture methods, group discussions, the use of visual media, and peer education approaches.In general, HIV/AIDS education has been shown to be effective in improving adolescent knowledge and attitudes. However, most studies still use relatively simple designs without control groups, so further research with a more robust methodological plan and long-term evaluation is needed to confirm the findings.